Płyta nagrobna z Borek (gmina Dąbrowa Chełmińska, pow. bydgoski) (Kronika Bydgoska, 2013)
The authors of this article made an attempt at answering the question about the genesis of the tombstone located on the limits of one of the three cemeteries in Borki village (Dąbrowa Chełmińska Commune). The article presents the beginnings of Borki village connected with Haulander settlement, the location of cemeteries and their layout. The tombstone found was located on the limits of the ”old” cemetery, which was to function as a ”simultaneous” Catholic-Protestant cemetery. The preserved part of the inscription informs that the Bolt family rested under it: two daughters and two sons, and their mother (Martin Bolt died in 1767). The tombstone, funded by the children’s father, is decorated with an antiquizing bas-relief depicting a group surrounded with a laurel wreath: a female and four children on an anchor. The authors opt for its Mennonite origin (due to its connections with north-German sepulchral art) and postulate archaeological examination at the cemetery in order to confirm or exclude its cemetery origin in connection with the assumption that this is the oldest tombstone preserved in the cemetery ”extra muros” in the voivodeship.